Exploring Sports Betting Prevalence, Patterns, Effects, And Associated Factors Among Undergraduate Students in a Nigerian University — A Cross-Sectional Study - Daniel, Faithful Miebaka; Gbuchie , Monica Anurika; Aniebiet, Charlie Monday; Emeruwa, Victoria Ezinne; Ike, Williams Ibangha (International Journal of Medical Students, 2023)
BACKGROUND: The rise of legalized gambling, fueled by technology and social media, has transformed betting into a risky economic activity that promises income. In Nigeria, sports betting has become increasingly popular among youths, particularly university students, with easy online access contributing to its prevalence. However, inadequate awareness of its risks and impact on academics persists due to the perception that sports betting lacks overt physical manifestations. Research is needed to increase understanding of sports betting's patterns, correlates, and impact, especially among undergraduates. AIMS: This study aimed to shed light on the prevalence, patterns, and implications of sports betting among undergraduates at the University of Calabar, to foster comprehensive solutions to address its negative consequences on academic performance and overall well-being. METHODS: A cross-sectional study was conducted on undergraduate students of a federal University in Nigeria. Multistage randomized sampling was utilized to recruit 406 participants for the study. Seventeen departments were selected using simple random sampling, and one class was chosen from each department through balloting, resulting in a total of 17 classes. Proportional allocation was used to determine the number of participants required from each class, and systematic sampling was employed to select the participants. Data was collected using a standardized questionnaire adapted from the British Gambling Prevalence Survey, with the Problem Gambling Severity Index used to assess the prevalence of problem gambling and the effects of sports betting on bettors. Motivations for sports betting were assessed using the Reasons for Gambling Questionnaire. The impact of sports betting on academics was evaluated using a separate set of questions. Data were analyzed using IBM SPSS version 26; p-values less than 0.05 were considered significant. RESULTS: Out of 406 undergraduate respondents, 36.7% had engaged in sports betting, with 30.3% participating in the past year. Among past-year gamblers, 21.9% bet as frequently as 2-3 days a week, 18.7% bet 2-3 days a month, and 15.40% bet daily. Football was the preferred sport for 95.9% of sports bettors. Two-thirds of past-year gamblers used online platforms for betting, while 32.5% utilized land-based venues. Most sports bettors (87.8%) were motivated by monetary consideration, while 10.5% did so out of fear of missing out. Advertisements influenced 56.1% of respondents' decisions to place bets. Problem gambling prevalence was 14.3% in the study population and 47.2% among past-year gamblers. Negative academic impacts were reported by 64.2% of past-year gamblers. In bivariate analysis, a p-value <0.05 was considered significant, and age, sex, and monthly income had a significant relationship with lifetime gambling prevalence. Sex and socioeconomic status were significantly associated with problem gambling. Regular gambling was significantly related to academic performance. CONCLUSION: Gambling is prevalent among undergraduates and a significant proportion develop addictive disorders like problem gambling requiring mental health rehabilitation. This study underscores the necessity of interventions, regulations, and support services to tackle the prevalence and consequences of sports betting among students. Recommendations include education campaigns, age verification, financial literacy programs, and support groups to empower students and address potential negative impacts.